Pelatihan Marketing Untuk Peningkatan Kapasitas Pengurus Koperasi Merah Putih Kecamatan Bangsal Mojokerto - Hidayat, M. Syamsul; Setyariningsih, Eny; Utami, Budi (Fakultas Ekonomi Universitas Islam Majapahit, 2026)
One of the government programs to increase economic activity is the establishement of the Koperasi Merah Putih Desa/Kelurahan (KDKMP) throughout Indonesia.For the success of this business,it ii necessary to be supported by the competence of human resources in the Village/City as Coperative administrators who carry out their business activities. While While the competence of human resources in the Village/City in managing cooperatives related to marketing management for sustainability is not yet fully evenly distributed. The purpose of this Community Service Activity is to provide knowledge and understanding of the Koperasi Merah Putih Desa/Kelurahan (KDKMP) Program as well as the management and marketing of Cooperative businesses through increasing the empowerment of Administrators. The Community Service Activity was carried out in the Bangsal District area of Mojokerto Regency and was attended by 110 Cooperative administrators. This activity provides marketing training to increase the capacity of cooperative managers, specifically in managing and marketing the Koperasi Merah Putih Desa/Kelurahan (KDKMP). The training method used is face-to-face meetings and interactive discussions, utilizing three modules: Business Plan Preparation and Risk Mitigation, Business Development, and Sustainable Marketing Management. The result is that Cooperative Management Partners gain an understanding and knowledge of cooperative business management and marketing, including business plan proposal preparation and risk mitigation, sustainable marketing management, and business development.